Empowering Indigenous Youth: A Strengths-Based Approach to Positive Development, Relationship Safety, and Community Building - Van Bavel, Marisa (Werklund School of Education, 2025)
This dissertation presents three interconnected manuscripts on various aspects of Indigenous youth wellness and the researcher’s journey in community-based research. The first paper (Chapter Two) provides a review of wellness factors that help Indigenous youth thrive. These factors are explored through the lens of the First Nations Mental Wellness Continuum framework. When cultural, social, and historical factors are prioritized, Indigenous youth may find hope, belonging, purpose, and meaning. Further, this review emphasises that culturally rooted initiatives empower Indigenous youth to build on their strengths. In paper two (Chapter Three), I utilized data from the nationally representative General Social Survey: Canadian’s Safety to explore Indigenous youths’ experiences of dating violence. Dating violence represents a manifestation of unhealthy relationship patterns that have emerged from colonial violence. Dating violence was significantly associated with age and gender, along with several social and psychological factors including religion, sense of belonging, and awareness of services. Findings illuminate the need for cultural and community supports as experiences of dating violence were significantly associated with poorer well-being among Indigenous youth. This secondary data analysis presents emerging insights into Indigenous youths’ experience of dating violence and offers some suggestions that can inform programming to support survivors. Finally, in paper three (Chapter Four), I share an autoethnography of my reflections observing Tsuut’ina Nation Police as they built a prevention and intervention program for youth who may be justice-system involved. This personal account sheds light on challenges and learning opportunities for Western researchers. I discuss the need to be flexible, respect local knowledge, and illustrate the practical application of principles discussed in previous chapters. This paper showcases the strengths of Tsuut’ina Nation, and the inherent capacity Indigenous communities have ...